Merdeka Belajar: the Real Learning Needs of Students, Teachers, and Institutions Related to Demands for Independent Learning Innovation - Fernandes Arung; Fathiaty Murthado; Endry Boeriswati (Universitas Muhammadiyah Surakarta, 2023)
This study aimed to identify real learning needs to meet the requirements of the 'Merdeka Belajar' [Freedom of Learning] concept initiated by the Indonesian Ministry of Education and Culture. This survey revealed the urgent needs of students, teachers, and institutions regarding implementing the 'Freedom of Learning' concept, as indicated by the responses of 1,935 teachers and students from various secondary schools in DKI Jakarta who completed self-designed questionnaires. These needs included freedom from formalities, adequate infrastructure, evaluation assessment systems aligned with the principle of free education, and full support from all stakeholders, particularly local government. The